Phenotypes of coronary microvascular obstruction phenomenon (no-reflow) during percutaneous coronary interventions in myocardial infarction - A. A. Frolov; I. A. Frolov; N. D. Ulanova; I. G. Pochinka; K. V. Kuzmichev; A. S. Mukhin; E. G. Sharabrin (Бюллетень сибирской медицины, 2024)
Objective: using the clustering method, to determine and describe the clinical and pathogenetic phenotypes of the coronary microvascular obstruction phenomenon (CMVO) that occurs during percutaneous coronary interventions (PCI) in patients with myocardial infarction (MI).Materials and methods: the study group included 190 patients with CMVO that occurred during PCI for type 1 MI. Participants admitted in 2013-2020. CMVO criteria: blood flow < 3 points in the infarct-related artery (IRA) according to TIMI flow grade (TFG); perfusion < 2 points for Myocardial blush grade; ST segment resolution < 70%. Median age – 64 [56; 70] years, 137 (72%) men, 53 (28%) women. MI with ST elevation (STEMI) in 170 patients (89%). Primary PCI in 127 (67%) cases. Nine patients (4.7%) have died. Phenotyping was performed using the EM (expectation-maximization) clustering algorithm.Results: three phenotypes have been identified in a ratio of 56% (n = 106) / 27% (n = 52) / 17% (n = 32). The values of the parameters are respectively: age 62 [54; 67] / 73 [67; 79] / 59 [50; 65] years; women 8 (8%) / 39 (77%) / 6 (19%); STEMI 102 (96%) / 43 (83%) / 25 (78%); thrombolysis 46 (43%) / 6 (12%) / 11 (34%); acute heart failure 1 [1; 2] / 2 [1; 4] / 2 [2; 2] class; platelet to lymphocyte ratio 110 [78; 153] / 106 [85; 132] / 132 [100; 182]; glucose at admission 8,0 [6,9; 9,6] / 11,1 [8,8; 15,2] / 7,5 [6,1; 8,1] mmol/l; total cholesterol 4,7 [4,2; 5,4] / 5,3 [3,7; 6,2] / 5,1 [4,5; 6,2] mmol/l; glomerular filtration rate according to CKD-EPI 77 [64; 88] / 58 [46; 74] / 81 [64; 88] ml/min/1.73m2; Syntax Score 15 [10; 21] / 20 [14; 26] / 8 [5; 10] points; Syntax Score in IRA 9 [8; 15] / 12 [7; 16] / 6 [3; 7] points; collaterals according to Rentrop 0 [0; 1] / 0 [0; 1] / 0 [0; 0] degree; TIMI thrombus grade 5 [5; 5]/ 5 [3; 5] / 1 [0; 2] degree; TFG 0 [0; 0] / 0 [0; 1] / 2 [2; 3] degree; aspiration thrombectomy 30 (28%) / 7 (13%) /4 (13%); IRA diameter 3,5 [3,0; 3,5] / 3,0 [2,8; 3,5] / 3,5 [3,0; 3,5] mm; balloon angioplasty 99 (93%) / 45 (87%) /16 (50%); PCI of 2 or more arteries 0 (0%) / 4 (8%) / 3 (9). Deaths – 2 (1.9%), 7 (13.5%) and 0 (0%) patients, respectively (p = 0.002, χ2-Pearson).Conclusion. Тhree phenotypes have been identified. First phenotype: severe IRA thrombosis, mostly men, moderate atherosclerotic lesions. Second phenotype: mostly elderly women, high hyperglycemia, severe atherosclerotic lesions, severe AHF, impaired renal function, IRA thrombosis. Third phenotype: mostly men, minor changes in the coronary arteries, absence of significant thrombosis and preserved blood flow in the IRA before PCI, elevated levels of inflammatory markers and total cholesterol.